On modelling electrets and piezoelectric actuators1. (19th December 2013) - Bossavit, Alain; Dupre, Luc; Geuzaine, Christophe
SUMMARY Electrets and piezoelectric components of various actuating devices require to take displacement currents into account, hence a less familiar modelling than in the eddy‐currents case. We review basic formulations and how to discretize them. Copyright © 2013 John Wiley & Sons, Ltd.